KUALITAS HADIS-HADIS DALAM FATWA MUI TENTANG COVID-19 - Aulia, Corry (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Hadith is one of the guidelines of Muslims in taking an ijtima 'or deeds that are not explained in the Qur'an. Muslims throughout the world must hold fast to the Qur'an and the hadith in carrying out religious law. Hadith is also an important source of Islam both functionally and structurally. Structurally the tradition has a second position after the Qur'an and functionally depends on where it is used and practiced. As a source of the teachings of Islam the Hadith always gets special attention from the scholars both in riwayah sanad and matan, both in the aspects of riwayah and in the raid. Therefore in the science of hadith it is very important to review or examine the quality of the traditions that are used before they are used as a legal basis or fatwa.Hadith is one of the guidelines of Muslims in taking an ijtima 'or deeds that are not explained in the Qur'an. Muslims throughout the world must hold fast to the Qur'an and the hadith in carrying out religious law. Hadith is also an important source of Islam both functionally and structurally. Structurally the tradition has a second position after the Qur'an and functionally depends on where it is used and practiced. As a source of the teachings of Islam the Hadith always gets special attention from the scholars both in riwayah sanad and matan, both in the aspects of riwayah and in the raid. Therefore in the science of hadith it is very important to review or examine the quality of the traditions that are used before they are used as a legal basis or fatwa.